Lesson Design Of Geometric Sequences Based On The 6-Question Cognitive Theory - Yujie Lin; Ying Zhou; Simin Wang; Tommy Tanu Wijaya (Journal on Education, 2020)
The effective teaching design of mathematics should be designed carefully by teachers according to the situation of students' learning and the analysis of teaching materials. Its teaching design should run through the origin and development of knowledge generation, and reasonably ensure the continuity and integrity of teaching. Based on the theory of "6-Question Cognitive Theory", This research using development method with steps to make comparisons between the this paper attempts to make a comparison between the "equal ratio sequence" and the "equal ratio sequence". Results in this study show that The teaching design of "6-Question Cognitive Theory" knowledge embodies the coherence, completeness and operability of the teaching design from six aspects: where the mathematical knowledge comes from, the essence of the knowledge, the connection and difference between the new knowledge and the old knowledge, the transformation of the knowledge, how to apply the knowledge and the process of reflecting the knowledge generation, so as to provide a theoretical and practical reference for the teaching design of high school mathematics Test